If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -2n = n + 2 Reorder the terms: 11 + -2n = 2 + n Solving 11 + -2n = 2 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 11 + -2n + -1n = 2 + n + -1n Combine like terms: -2n + -1n = -3n 11 + -3n = 2 + n + -1n Combine like terms: n + -1n = 0 11 + -3n = 2 + 0 11 + -3n = 2 Add '-11' to each side of the equation. 11 + -11 + -3n = 2 + -11 Combine like terms: 11 + -11 = 0 0 + -3n = 2 + -11 -3n = 2 + -11 Combine like terms: 2 + -11 = -9 -3n = -9 Divide each side by '-3'. n = 3 Simplifying n = 3
| H-4/j | | 6(3x-4y+8z)=0 | | 30x+5=31x+2 | | 4xy/2x | | 3(-10-11p)+10(4p+6)=30 | | 3a-4a=5(a-3) | | n+4n=235 | | t/14=-3 | | 245=15m+125 | | 3/1=-1/2a | | 5*x+1=24 | | 10=5+b | | 13+3x=8n-3(n-4) | | 4y/9=-16 | | 3/14x4 | | x^6=24 | | x/2-=-5 | | 16x-15-8x=13 | | 2cosx-3sinx=5 | | 8/11÷33/40 | | .66d=8 | | P^2+13p=-40 | | (t-12)=27 | | 10-6n=24n | | 2(3x-4)=6x+8 | | d/21=1.5/3.5 | | 2(x-3)=(x+1)+7 | | 3x*2=30 | | 4(x-1.9)=9.3 | | Fm=5y+13 | | 5(x+6)=30 | | 4m^2+9m=0 |